(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2023)
Since the beginning of the 21st century, the countries of the Middle East have experienced several episodes of revolt and revolution. Art in general has both been affected by and has influenced these events. With this in mind, my essay examines the art of puppet theatre as an epic narrative approach in the sense of both epic-political and epic-adventurous. To explore this phenomenon in historical context, I first trace puppetry’s past in the Middle East and then discuss in more detail its important contemporary role. My contention is that the Middle Eastern puppet becomes a narrative schema of the socio-political field, going beyond the limits imposed on the rest of society with skill, like a hero who acts to save his beloved at the end of the story.